The Role of Special Child Development Institutions (LPKA) in the Psychological Rehabilitation of Children from Broken Home Families - Zubaidah Zubaidah; Devi Haryani Putri; Atria Afrilianti; Iktibar Iktibar (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Children from broken home families often face significant psychological challenges, including anxiety, depression, low self-esteem, and difficulties in building healthy social relationships. Special Child Development Institutions (LPKA) play a crucial role in addressing these challenges and supporting the psychological rehabilitation of such children. This study was conducted in 2024 at the LPKA in Bengkulu City. Objective: This study aims to explore the psychological challenges faced by children, such as anxiety, depression, low self-esteem, and difficulties in building healthy social relationships. The research was conducted in 2024 at the Special Child Development Institution (LPKA) in Bengkulu City. Method: This research employed a case study approach. Data were collected through in-depth interviews, participatory observations, and documentation. The data analysis utilized thematic analysis. Result: LPKA Bengkulu, as an institution, aims to (1) Provide guidance to children based on restorative justice principles; (2) Ensure the fulfillment of children's rights; (3) Facilitate the reintegration process of children into their family and community environments. Conclusion: These children have the potential to improve their psychological well-being and prepare themselves for better reintegration into society. Contribution: This study contributes to academic literature on the role of rehabilitation institutions in supporting children's psychological development, particularly from the perspective of interventions for children from broken homes.